EXPLORING ENGLISH STUDENT TEACHERS’ READING HABITS AND PREFERENCES - Muhsiyana Nurul Aisyiyah; Mohammad Andi Hakim (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
The vast benefits of reading in both the first and the target language makes reading essential for English Language Teaching Department students who are not only English language learners but also English teacher candidates. This study explores English student teachers’ reading habits and preferences. An open-ended and closed-ended questionnaire and interviews were used to collect information on 88 English student teachers’ reading habits and preferences. The participants’ reading habits were predicted by their attitudes towards reading, reading frequency, and reading material preferences. The findings suggest that although student teachers mostly displayed positive attitudes towards reading and acknowledged the importance of reading, they didn’t really invest in personal reading. In terms of reading preferences, most of the student teachers chose fiction books and online materials as the most preferred reading materials. When it comes to language preferences, most of them preferred to read in their first language (Indonesian) instead of the language they are currently learning (English) for both academic reading and reading for pleasure.